Sustainable Jatropha oil-based membrane with graphene oxide for potential application in Cu(II) ion removal from aqueous solution - Harun, Nur Haninah; Zainal Abidin, Zurina; Abdullah, Abdul Halim; Othaman, Rizafizah (MDPI, 2020)
More recent attention has been focused on the utilization of Jatropha curcas in the field of water treatment. The potential of Jatropha oil in the synthesis of membrane for water filtration had been explored, its performance compared to the addition of graphene oxide (GO) in the polymer matrix. Jatropha oil was modified in a two-step method to produce Jatropha oil-based polyol (JOL) and was blended with hexamethylene diisocyanate (HDI) to produce Jatropha polyurethane membrane (JPU). JPU was synthesized in different conditions to obtain the optimized membrane and was blended with different GO loading to form Jatropha/graphene oxide composite membrane (JPU/GO) for performance improvement. The synthesized pristine JPU and JPU/GO were evaluated and the materials were analyzed using fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), contact angle, water flux, and field emission scanning electron microscopy (FESEM). Results showed that the ratio of HDI to JOL for optimized JPU was obtained at 5:5 (v/v) with the cross-linking temperature at 90 °C and curing temperature at 150 °C. As GO was added into JPU, several changes were observed. The glass transition temperature (Tg) and onset temperature (To) increased from 58 °C to 69 °C and from 170 °C to 202 °C, respectively. The contact angle, however, decreased from 88.8° to 52.1° while the water flux improved from 223.33 L/m2·h to 523.33 L/m2·h, and the pore distribution in JPU/GO became more orderly. Filtration of copper ions using the synthesized membrane was performed to give rejection percentages between 33.51% and 71.60%. The results indicated that GO had a significant impact on JPU. Taken together, these results have suggested that JPU/GO has the potential for use in water filtration.